The journal of electronic publishing JEP. (University of Michigan Press, 1995)
Presents the "Journal of Electronic Publishing," published monthly by the University of Michigan Press. Contains feature articles and editorials. Allows users to browse back issues by subject, title, or author. Highlights subscription information, a list of the members of the editorial board, and authors' guidelines.